Anticoronavirus activity of C60 fullerene: in silico and in vitro screening - Василь Гурмач; Вячеслав Караушу; Зінаїда Клестова; Володимир Берест; Юрій Прилуцький (Біофізичний вісник)
Background: The search for potential therapeutic agents against the most common coronaviruses, which can pose a threat to human and animal life, is an urgent issue of modern biomedicine.